Giant magnetoresistance in La0.7Pb0.3MnO3 thin film - Khartsev, S. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
Epitaxial thin films of La0.7Pb0.3MnO3 have been grown on (100) LaAlO3 and (110) SrTiO3 substrates by dc magnetron sputtering. The magnetic-field and temperature-dependent resistivity of as-deposited and post-annealed films was examined. At H=10kOe the maximum observed magnetoresistance ratio (R0-RH)/R0 was 62%. The bolometric response to 0.94- m low-frequency modulated radiation in the film with the temperature coefficient of resistance dlnR/dT= 14% was studied. The transport properties are described using Zhang`s spin-polaron theory. An unusual approach to stabilizing the film temperature at the point corresponding to the maximum of the magnetoresistance ratio and responsivity is discussed.